THE LABORIOUS PROTECTION OF FUNDAMENTAL RIGHTS OF EXILED PEOPLE - ZACHAYUS, Anna (MEDECINE LEGALE DROIT MEDICAL, 2025)
The Defender of Rights and the National Consultative Ethics Committee once again warn of the inadequacy and ineffectiveness of the protection of the fundamental rights of exiled people. These people, as human beings, must enjoy the protection of some rights. But the effectiveness of the latter is today called into question, in particular because of the failure of legal and extra-legal mechanisms for the protection of fundamental rights.